2016
DOI: 10.1371/journal.pone.0151728
|View full text |Cite
|
Sign up to set email alerts
|

Sporadic Retinoblastoma and Parental Smoking and Alcohol Consumption before and after Conception: A Report from the Children’s Oncology Group

Abstract: BackgroundRetinoblastoma is the most frequent tumor of the eye in children and very little is known about the etiology of non-familial (sporadic) retinoblastoma. In this study we examined whether parental tobacco smoking or alcohol consumption (pre- or post-conception) contribute to the two phenotypes (bilateral or unilateral) of sporadic retinoblastoma.MethodsTwo large multicenter case-control studies identified 488 cases through eye referral centers in the United States and Canada or through the Children’s O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 37 publications
1
22
1
4
Order By: Relevance
“…Children with bilateral retinoblastoma carry a germline mutation in one allele of a retinal progenitor cell, due to RB1 inheritance from a parent, de novo mutation in parental germline cells or due to a mutation that occurs during very early embryonic development; these children lose the second allele somatically during the pregnancy. Only a small number of studies have reported on maternal smoking and retinoblastoma, but several have reported increased effect estimates . Of these, one study reported an increased risk for maternal smoking in the first trimester and bilateral retinoblastoma (OR = 3.7), and another study an increase with sporadic heritable disease (OR = 2.0), which typically presents as bilateral; the third study did not stratify by laterality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Children with bilateral retinoblastoma carry a germline mutation in one allele of a retinal progenitor cell, due to RB1 inheritance from a parent, de novo mutation in parental germline cells or due to a mutation that occurs during very early embryonic development; these children lose the second allele somatically during the pregnancy. Only a small number of studies have reported on maternal smoking and retinoblastoma, but several have reported increased effect estimates . Of these, one study reported an increased risk for maternal smoking in the first trimester and bilateral retinoblastoma (OR = 3.7), and another study an increase with sporadic heritable disease (OR = 2.0), which typically presents as bilateral; the third study did not stratify by laterality.…”
Section: Discussionmentioning
confidence: 99%
“…Only a small number of studies have reported on maternal smoking and retinoblastoma, but several have reported increased effect estimates . Of these, one study reported an increased risk for maternal smoking in the first trimester and bilateral retinoblastoma (OR = 3.7), and another study an increase with sporadic heritable disease (OR = 2.0), which typically presents as bilateral; the third study did not stratify by laterality. Our findings for astrocytoma support those seen in another prospective investigation …”
Section: Discussionmentioning
confidence: 99%
“…Detailed methods were previously published 10. Briefly, study approval was obtained by each participating COG institution, Wills Eye Institute, the University of Pennsylvania and the University of California, Los Angeles.…”
Section: Methodsmentioning
confidence: 99%
“…24, 25 In brief, eligible incident cases were diagnosed with sporadic retinoblastoma on or after July 1 st , 2006 through June 30, 2011 and were diagnosed and/or treated at a COG institution or at the Wills Eye Institute in Philadelphia, PA, USA. Cases were eligible if they were residing in the U.S. or Canada, had access to a home or cellular telephone, and had at least one biological parent who spoke English or Spanish that was available for participation.…”
Section: Methodsmentioning
confidence: 99%
“…Selection of variables for adjustment was based upon literature review as well as associations observed in our data. 23, 2529 In analyses involving unilateral cases we adjusted for mother’s race (White non-Hispanic, Hispanic, Other), mother’s employment status (Yes/No), whether the father was living at home at the start of pregnancy (Yes/No), and the mother’s age (<29, 30–34, 35+). In analyses of bilateral retinoblastoma, we adjusted for the same variables with the addition of father’s age (<29, 30–34, 35+).…”
Section: Methodsmentioning
confidence: 99%